LEXICAL EXPRESSIVITY AND ITS POTENTIAL TO VIOLATE THE OBJECTIVITY IN NEWS REPORTING - Jílek, Viktor (Bohemica Olomucensia, 2021)
Evaluative expressives undermine the objectivity of news reporting. To identify them, a complex taxonomy has been created. Subsequent analysis of television news has shown a high frequency of use of evaluation expressions in the statement, moreover contextually connected with other evaluation units.
Keywords: Expressivity; information quality; informative functions; lexicology; manipulation; mass media; objectivity; preferred reading; sememe evaluation; stylistics; narrative context; Westerståhl; news.